Conformationally Restricted Dipyrromethene Boron Difluoride (BODIPY) Dyes: Highly Fluorescent, Multicolored Probes for Cellular Imaging - Zheng, Qingdong; Xu, Gaixia; Prasad, Paras N. (Chemistry : a European journal, 2008)
Novel fluorescent, conformationally restricted dipyrromethene boron difluoride (BODIPY) dyes have been prepared by introducing a naphthalenyl group at the meso position of the BODIPY core. These BODIPY dyes exhibit increased fluorescence quantum yields compared with dyes that have a meso‐position phenyl group with internal rotation. The absorption and emission wavelengths of such conformationally restricted BODIPY dyes can be easily tuned to the near‐IR range by derivatization through a condensation reaction with benzaldehyde derivatives. The two‐photon absorption properties of these BODIPY dyes were also investigated and the results show that they exhibit increased two‐photon excited fluorescence compared to analogue dyes that contain a phenyl group. The one‐ and two‐photon fluorescence imaging of living cells by using selected BODIPY dyes has been successfully demonstrated. Green for go! Highly fluorescent BODIPY dyes that emit light ranging from the green to near‐IR region have been synthesized by introducing a bulky naphthalenyl group at the meso position. The one‐ and two‐photon fluorescence imaging of living cells with these dyes has been successfully demonstrated (see graphic).